Staphylococcus aureus: the paths and crosstalks that lead to heme - Videira, Marco A.M (2020)
Tetrapyrroles are biological molecules widespread through all living organisms and necessary for fundamental cellular processes. Within the wide range of known tetrapyrroles, heme and siroheme are prosthetic groups in proteins responsible for important functions such as gas transport and storage, electron transport, cellular signaling, cellular detoxification as well as for reduction of sulfite and nitrite. Both molecules are synthesized from a last common tetrapyrrole precursor, namely uroporphyrinogen III, forming heme via four enzymatic steps know as the classical heme biosynthesis pathway and generating siroheme via an independent route. In some organisms such as sulfate and nitrate reducing bacteria, heme is alternatively synthesized through the siroheme-dependent pathway. (...)